Ethnomathematics: Exploring Geometric Shapes and Patterns in Sasak Snacks - Rahmawati, Fitri Indah; Hastuti, Intan Dwi; Mariyati, Yuni; Syaharuddin, Syaharuddin (Universitas Muhammadiyah Sumatera Utara (UMSU), 2026)
Mathematics is often perceived as a discipline that is separate from everyday reality and has little connection to the cultural context of society. Historically, however, mathematics grew and developed from the social practices of communities, including local culinary traditions. Sasak traditional snacks, as part of cultural heritage, not only have aesthetic and symbolic value, but also contain mathematical structures that can be studied to bring geometric concepts closer to the cultural reality of society. This study aims to identify and analyze the geometric shapes and patterns contained in the traditional snacks of the Sasak community in Montong Tangi Village, East Sakra District, East Lombok Regency, through an ethnomathematics perspective.This study uses a qualitative approach with an ethnographic design. Data were collected through direct observation and ethnographic interviews with traditional snack makers, traditional leaders, and community leaders who understand Sasak culinary traditions. Data analysis was carried out interactively through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through source triangulation.The results show that traditional snacks such as cerorot, lupis, jaje abuq, and renggi represent various geometric concepts, including cones, triangular prisms, circles, and triangular pyramids, which are formed through traditional techniques of folding, compacting, and wrapping ingredients. These geometric representations are not only structural in nature, but also contain cultural values such as perseverance, togetherness, and harmony, which are reflected in the traditional practices of the Sasak people. These findings confirm that traditional Sasak snacks have the potential to be a relevant source of contextual learning to enrich culture-based geometry learning.